Odd Harmonious Labeling of Lotus Flower Graphs - Fery Firmansah; Tasari Tasari; Muhammad Ridlo Yuwono (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2025)
The purpose of the research is to obtain the construction of a new graph class definition and the new graph class satisfies the properties of odd harmonious labeling. The research method consists of a preliminary stage, namely the stage of finding open problems, the stage of analyzing data for the formation of definitions and theorems, the stage of verifying the results of proving the theorems mathematically. The research results obtained three new graph class definitions, namely the definition of lotus flower graph, the definition of lotus flower graph with pendant, and the definition of lotus flower graph variation. Furthermore, it has been proven that lotus flower graph, lotus flower graph with pendant, and variation of lotus flower graph satisfy the properties of odd harmonious labeling so that they are odd harmonious.